Asymmetric nucleophilic substitutions to construct all-carbon quaternary stereocenters under PTC conditions - Ban, Xu (2019)
Nucleophilicity and nucleophilic substitution is one of the most important concepts and processes in organic chemistry. Traditionally, the term nucleophilic substitution in organic chemistry implies substitution exactly at the carbon atom, but there is a rather wide class of reactions in which the nucleophile attacks a halogen atom but not the carbon atom, such reactions, then are named halophilic or halogenophilic reactions and proceeded by SNX route. Herein we describe a novel asymmetric nucleophilic substitution to construct all-carbon quaternary stereocenters under PTC conditions. In this reaction, the C-Br bond is cleaved to generate a newly C-C bond with high enantioselectivity. Different kinds of tertiary bromides with electron withdrawing groups are proved to be excellent electrophiles for malonates under a base condition. We envisioned that the breakthrough of the C-halogen bond is proceed by a SNX route and our guanidiniums PTC induce the formation of the all carbon quaternary canter. This concept provide a new direction for the development of nucleophilic substitutions.